2005
DOI: 10.1097/01.alc.0000156084.27547.ec
|View full text |Cite
|
Sign up to set email alerts
|

The Privatization of Wine Sales in Quebec in 1978 and 1983 to 1984

Abstract: The estimated effect of the policy change in 1978 was modest compared with results presented in most earlier studies regarding the privatization of wine sales in other jurisdictions. One explanation could be that the policy change in Quebec was valid only for a limited number of wines, which accounted for only a fraction of the total alcohol sales market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…These changes resulted in a marked increase in the consumption of beer, with marginalised and heavy drinkers affected more than the average. Similar results were found when the privatisation of wine sales in Quebec was studied [23]. In contrast, similar studies in Norway found little effect on total alcohol consumption when beverage-specific (beer) outlet densities changed.…”
Section: Effects On Alcohol Consumptionsupporting
confidence: 77%
“…These changes resulted in a marked increase in the consumption of beer, with marginalised and heavy drinkers affected more than the average. Similar results were found when the privatisation of wine sales in Quebec was studied [23]. In contrast, similar studies in Norway found little effect on total alcohol consumption when beverage-specific (beer) outlet densities changed.…”
Section: Effects On Alcohol Consumptionsupporting
confidence: 77%
“…As it was outlined earlier, there are few studies in Canada that have estimated the effect of privatisation in terms of changes in alcohol consumption/sales. Trolldal reported that the effect of the liberalisation of wine sales in 1978 in Quebec resulted in a permanent effect on wine sales, which increased by 10% [10]. Trolldal also studied the privatisation of the retail sale of all alcohol in Alberta between 1980 and 1990 and reported that sale of spirits increased by 12%, but sales of wine and beer were not significantly affected [9].…”
Section: Design and Methodsmentioning
confidence: 99%
“…As a result, in Alberta, a significant and permanent effect on the sale of spirits was observed, but the effect was not large enough to affect total sales [9]. Likewise, Trolldal [10] reported a significant and permanent effect of the policy change in Quebec in 1978 with the sale of wine increasing by 10%. Stockwell et al .…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…Specifi cally, the introduction of large numbers of stores resulting from partial privatization was associated with increases in alcohol consumption (Stockwell et al, 2009), alcohol-related mortality (Stockwell et al, 2011), and lower alcohol prices (Treno et al, 2013). On the other hand, there have been contrary fi ndings (Mulford et al, 1992;Trolldal, 2005aTrolldal, , 2005b. Thus, the data do seem to indicate that monopoly controls are typically associated with more positive public health outcomes.…”
Section: Privatization Effectsmentioning
confidence: 99%